The Effect of PKN Lessons in Improving the Students Spirit of Nationalism of the National Awakening in1908 of Eight Grade Students SMP Negeri 4 Siborongborong - Dinata Lumban Gaol; Torus M. Sianturi (Institute of Computer Science (IOCS), 2021)
This research is the attitude or behavior shown by students in reflecting the very low spirit of nationalism the lack of students' motives for enthusiasm in learning to increase the spirit of nationalism in these students. This study aims to determine the influence of Civics Subjects in Increasing the Spirit of Nationalism in Students in the Materials. The subject of the study is eight grade Students of SMP Negeri 4 Siborongborong which number of students is 31 people. The data collected was in the form of data from the observations of researchers and the results of questionnaires given to students. The results showed that the attitude or behavior shown by students their statements and knowledge in reflecting the spirit of nationalism increased. From the data analysis in cycle I and cycle II, the percentage of observation results in cycle I was 42% and the percentage of observations in cycle II was 75%. The results of the average value of the questionnaire given in the first cycle is 62 (below the KKM 75) and the average value of the questionnaire given in the second cycle is 86 (above the KKM 75), each with a less good category. Based on the analysis of the data above, it can be concluded that there is an influence of Civics Subjects in Increasing the Spirit of Nationalism in Students on the Main Material